Compass and clock : poems - Sanders, David, 1955 March 4- (Swallow Press/Ohio University Press, 2016)
"The poems of Compass and Clock take their inspiration from the intersection of the natural world and the human, exploring the landscapes in which those intersections occur. Those landscapes range from David Sanders's native midwestern countryside to the caves of Lascaux and an enchanted lake where relics of lost lives are washed ashore. Yet, the true source of the poems' vitality is Sanders's attention to the missed or misread moments, those times when the act fails, and the perceived clashes with the actual. Here, the satisfying pairing of elegance and vulnerability invites the reader to tour those uncanny landscapes from which one returns irrevocably changed?-?refreshed, but wistful. In a review of his earlier limited-edition work, Time in Transit, the Hudson Review called David Sanders "a poet to watch." With the Swallow Press publication of Compass and Clock, we have the realization of that promise"--